The Complementary Role of UI-LISA in Statistical Training and Capacity Building at the University of Ibadan, Nigeria - Adepoju, Adedayo A.; Olubusoye, Olusanya E.; Ogundunmade, Tayo P.; Oyelakin, Tomiwa T.; Robert, Bbosa (Promoting Statistical Practice and Collaboration in Developing Countries, 2022)
A notable gap in the statistical training at the tertiary level in Nigeria is the absolute lack of exposure to first-hand statistical practice and/or acquisition of statistical consulting skills by the students. At the University of Ibadan (UI), undergraduate students in statistics are required to undertake work experience for 3 months in industry or a government agency as part of the requirements for the awarded degree. Unfortunately, this requirement is not integrated into the curriculum of all statistics-degree-granting institutions in Nigeria. Even where the requirement exists, the challenge usually faced by the students is how to find suitable placements in a statistics-practice environment where practical statistical skills needed to become effective professional statisticians can be easily acquired. The creation of the UI Laboratory for Interdisciplinary Statistical Analysis [UI-LISA] in 2015 provided the needed environment for acquiring practical training in statistics. The objective of this chapter is to share how UI-LISA is serving as an industrial training (IT) resource base for statistics students seeking a place for their internship, not only from UI but also from neighbouring polytechnics and universities. From 2015 till date, UI-LISA has admitted and trained students under the IT platform created for them to acquire requisite experience for a period ranging from 3 to 6 months. These students have come from other institutions such as The Polytechnic Ibadan; Federal University of Technology, Akure (FUTA); Federal School of Statistics (FSS), Ajibode, Ibadan; Federal University of Agriculture, Abeokuta (FUNAAB) and Obafemi Awolowo University (OAU). The chapter describes the various activities undertaken at UI-LISA to complement statistical training at different levels of statistics education in Nigeria (such as National Diploma, Higher National Diploma, Bachelor's degree and Postgraduate). The main activities include: specialised hands-on training in statistical tools and software such as R; statistical consulting practices and training with clients; statistical collaboration skills; statistical communication; and a walk-in statistical clinic where statistical advice is provided to members of the university community. In sum, UI-LISA is positioned towards building statistical capacity and providing practical skills beyond the formal training provided by the institutions. A notable gap in the statistical training at the tertiary level in Nigeria is the absolute lack of exposure to first-hand statistical practice and/or acquisition of statistical consulting skills by the students. The objective of this chapter is to share how UI-LISA is serving as an industrial training resource base for statistics students seeking a place for their internship, not only from UI but also from neighbouring polytechnics and universities. Statistical education in the 21st century has continued to receive increasing attention by researchers and vigorous advocacy by professional statistical associations. With growing unemployment in Nigeria and the popular slogan of "unemployable graduates" from employers of labour, universities in Nigeria have been under serious pressure to help policymakers redress the trend. Statistics education has been expanding rapidly in Nigeria since independence in 1960. A good number of tertiary institutions including polytechnics and universities now offer statistics programme in Nigeria compared to the pre-independence situation.